2007 7th IEEE-RAS International Conference on Humanoid Robots 2007
DOI: 10.1109/ichr.2007.4813875
|View full text |Cite
|
Sign up to set email alerts
|

Drum-mate: A human-humanoid drumming experience

Abstract: Abstract-We present an exploratory study investigating a drumming experience with Kaspar, a humanoid child-sized robot, and a human. In this work, our aim is not to have Kaspar just replicate the human partner's drumming, but to engage with the human in a 'social manner' using head gestures in a call and response turn-taking interaction and to assess the impact of nonverbal gestures on the interaction. Results from the first implementation of a human-robot interaction experiment are presented and analysed qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…This first version of the Kaspar robot was used for a number of activities and games that encouraged skills such as turn taking to the exploration of facial expressions [13][14][15][16]. Further to this the robot was also used to explore the possibility of conducting robot-mediated interviews with children [17][18][19][20] and to explore interaction dynamics and gestures in human-humanoid drumming experiments [21,22] The second implementation of the Kaspar robot K1-L was built in 2006 and was similar in construction to the K1 version but was a much larger robot using a 6-year old child dummy as a chassis measuring approximately 123cm in height by 30 cm wide and 57 cm deep. This version of Kaspar was mounted on a desktop PC and was equipped with an extra DOF in each arm, providing the robot with a total of 18 DOF.…”
Section: The First Kaspar Robot (K1)mentioning
confidence: 99%
“…This first version of the Kaspar robot was used for a number of activities and games that encouraged skills such as turn taking to the exploration of facial expressions [13][14][15][16]. Further to this the robot was also used to explore the possibility of conducting robot-mediated interviews with children [17][18][19][20] and to explore interaction dynamics and gestures in human-humanoid drumming experiments [21,22] The second implementation of the Kaspar robot K1-L was built in 2006 and was similar in construction to the K1 version but was a much larger robot using a 6-year old child dummy as a chassis measuring approximately 123cm in height by 30 cm wide and 57 cm deep. This version of Kaspar was mounted on a desktop PC and was equipped with an extra DOF in each arm, providing the robot with a total of 18 DOF.…”
Section: The First Kaspar Robot (K1)mentioning
confidence: 99%
“…Also, different from the above-mentioned work with KISMET, where the interaction was the goal in itself, we wanted to include a certain (enjoyable) task that needs to be achieved jointly by the human-robot pair, to provide the overall context. Drumming is relatively straightforward to implement and test, and can be implemented technically without special actuators like fingers or special skills or abilities specific to drumming [12]. There are several works concerning drumming in human-robot interaction.…”
Section: Introductionmentioning
confidence: 99%
“…In the first presented study, turn-taking is deterministic and head gestures of the robot accompany its drumming to assess the impact of non-verbal gestures on the interaction [2]. The second study focuses on emergent turn-taking dynamics; here our aim is to have turn-taking and role switching which is not deterministic but emerging from the social interaction between the human and the humanoid [3].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the robot is not just 'following' and imitating the human, but can be the leader in the game and being imitated by the human. Details of the two studies summarized in this paper as well as related work can be found in [2,3]. 1 Acknowledgements: This work was conducted within the EU Integrated Project RobotCub ("Robotic Open-architecture Technology for Cognition, Understanding, and Behaviours"), funded by the EC through the E5 Unit (Cognition) of FP6-IST under Contract FP6-004370.…”
Section: Introductionmentioning
confidence: 99%